2019
DOI: 10.1111/tbj.13290
|View full text |Cite
|
Sign up to set email alerts
|

Local recurrence of breast cancer: Salvage lumpectomy as an option for local treatment

Abstract: Introduction The best local management for breast cancer recurrence following conservative treatment for breast cancer (BC) continues to be an open question. In this study, we compared patients' outcome after salvage lumpectomy (SL) vs mastectomy for ipsilateral breast tumor recurrence (IBTR). Materials and methods Between 1987 and 2014 we identified 121 patients with pT0‐2, N0‐3, M0 BC who had BCT as their primary treatment, and subsequently had IBTR (unifocal). 47 patients underwent SL and 74 salvage mastect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
(72 reference statements)
2
4
0
1
Order By: Relevance
“…Some studies reported that RBCS was not worse than SM ( 12 , 13 , 15 , 21 , 26 , 28 ), and some studies reported the opposite results ( 8 , 10 , 11 , 14 ). Other studies asserted that it did not suggest a worse prognosis, although the SLRR of RBCS was higher ( 25 ), which is consistent with our conclusions. The SLRR of RBCS was approximately7-31% ( 8 , 13 , 14 , 29 , 30 ), and the SLRR of SM was approximately 3-32% ( 8 , 13 , 21 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Some studies reported that RBCS was not worse than SM ( 12 , 13 , 15 , 21 , 26 , 28 ), and some studies reported the opposite results ( 8 , 10 , 11 , 14 ). Other studies asserted that it did not suggest a worse prognosis, although the SLRR of RBCS was higher ( 25 ), which is consistent with our conclusions. The SLRR of RBCS was approximately7-31% ( 8 , 13 , 14 , 29 , 30 ), and the SLRR of SM was approximately 3-32% ( 8 , 13 , 21 ).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, no significant difference in prognosis was observed in our study despite the lower SLRR of RBCS after IBTR than SM. This conclusion is similar to Sellam Y et al (25).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Исследования, которые отражают отсутствие статистически значимой разницы (в 5-летней безрецидивной и общей выживаемости) между ОСО c последующей дистанционной лучевой терапией (ДЛТ) и радикальной мастэктомией (РМЭ) были проведены десятилетия назад. Результаты исследований сыграли решающую роль в изменении парадигмы хирургического лечения РМЖ [4][5][6]. За последние годы опубликовано несколько ретроспективных исследований, в которых отмечено преимущество ОСО перед РМЭ по общей выживаемости [7][8][9].…”
Section: список сокращенийunclassified